Informator . no. 16, 1981 - "Solidarność" Biuro Informacyjne Zarządu Regionu Środkowo-Wschodniego (NSZZ "Solidarność" Region Środkowo-Wschodni, 1981)
Creation and circulation: After introduction of the Martial Law publication suspended. Republished underground in January 1982